SOSIALISASI PELAYANAN INFORMASI DALAM MENINGKATKAN KEPUASAN PENGGUNA JASA INFORMASI BANDAR UDARA MOPAH MERAUKE - Paul Adryani Moento; Nur Jala; Serly Susanti Ndun (Yayasan Perguruan Kampus, 2024)
Community service aims to enhance user satisfaction with information services at Mopah Airport, Merauke, through effective information service socialization. The method used involves a participatory approach, engaging airport management, information service staff, and the local community in designing and implementing the socialization program. Socialization activities include counseling, staff training, and distribution of easily understandable information materials for service users. Evaluation is conducted to assess the impact of socialization on user satisfaction with information services. The results show a significant improvement in users' understanding of airport information services and an increase in their satisfaction with the services provided. The implication of this community service underscores the importance of collaboration among the airport authorities, staff, and the local community in enhancing the quality of information services at the airport. Thus, this community service makes a valuable contribution to improving user experience with information services at Mopah Airport, Merauke, and promoting sustainable development at the local level.